Implementasi Metode Linear Congruential Generator pada Game Puzzle Kesenian Tari - Diana Nawang Safitri (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
Dance is a branch of Indonesian art that uses body movements and is performed rhythmically with the aim of expressing feelings or conveying individual or group messages. In this puzzle application, users are given two-level choices, namely 2x3 and 3x3. This puzzle game has the theme of Dance in Java, which is aimed at children aged 6-10 years. In this game application, there are several pictures from various provinces on the island of Java that have been converted into a puzzling view which later the user can arrange the pieces of the image. This design applies the Linear Congruential Generator (LCG) method as a randomizer for the images presented in this application. Based on the test results, it was found that this application was running in accordance with the initial concept and the application of the method was successfully applied.